Value of initial C‐reactive protein levels in status epilepticus outcome prediction. (20th February 2021) - Madžar, Dominik; Reindl, Caroline; Mrochen, Anne; Hamer, Hajo M.; Huttner, Hagen B.
Abstract: The role of neuroinflammation in the pathophysiology of seizures is increasingly recognized, and the evaluation of potential biochemical markers of inflammatory processes in seizures and status epilepticus (SE), such as C‐reactive protein (CRP), has gained attention. The present study assessed the first CRP level obtained in an SE episode regarding its value for SE outcome prediction. Among 362 admissions for SE during the study period, 231 episodes satisfied the inclusion criteria. Higher initial CRP concentrations were independently associated with in‐hospital mortality and poor functional outcome at discharge in logistic regression models adjusting for SE severity, severity of SE etiology, and development of treatment refractoriness. Therefore, initial CRP levels may add to the prediction of SE prognosis. The pathomechanisms through which CRP is linked with the prognosis of SE, however, remain to be established.